PENGARUH METODE PEMBELAJARAN BUZZ GROUP TERHADAP HASIL BELAJAR SISWA - Helmi, Ahmad; Baysha, Muhammad Husein (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
In learning Indonesian, methods and approaches have been used to improve results. One of them is to form students into discussion groups that are very beneficial for students. But the reality is not many teachers do it. The learning methods undertaken by teachers tend to be limited to the delivery of lectures, giving examples of questions, exercises and ending with assignments to be done at home. Many teachers still use the conventional approach so that the learning process only takes one direction where the teacher explains and students hear or take notes, so that there is often a tendency to minimize student involvement. The aim of this research is to find out the influence of buzz group learning methods on student learning outcomes in Indonesian VII Class subjects in MTs NW Pepao, Central Lombok District, 2018/2019 Academic Year. The formulation of the problem in this study is whether there is an influence of the buzz group learning method on student learning outcomes in Indonesian VII Class subjects in MTs NW Pepao, Central Lombok District 2018/2019 Academic Year. The learning method used in the sampling technique in this study is using random rampling techniques. Data collection techniques in this study used the test method as the main method while the documentation, as a complementary method. Data analysis techniques using statistical analysis with the t-test formula. The analysis results obtained a t-value of 4.882 and a table value at the Significance level of 5% with d.b (N-1) = 30-1 = 29 greater than the value of t in the table (4.882> 2.045), meaning that Ho is rejected and Ha is accepted.